Reabilitação e ampliação de edifício multifamiliar - Pires, Vasco António Martins Costa (2019)
This report falls within the scope of the final work of the master’s degree in urban rehabilitation at the polytechnic institute of Tomar. The internship took place in the Casa Gomes Engineering company and had as objective, the accomplishment of projects of the different specialties in the Engineering area. This internship report was based on the rehabilitation and expansion of a multifamily housing building located in Lisbon. In the early stages, it was made the geometric and photographic survey of the building to begin to study how best to rehabilitate it. During a meeting, the decision taken by the building owner and the technical team was the total demolition of its interior as it was extremely degraded, maintaining solely the exterior walls. Furthermore, the Municipal Plan Director of Lisbon allowed to expand an extra floor for the housing. The necessary conditions was reunited to start the phase of the project. Taking into account my involvement to develop some of the projects presented, I believe it must raise up to better frame this report. The projects in which I collaborated were: acoustic verification, distribution of building water, drainage of waste and rain water, ventilation and exhaust fumes and moreover, on track occupancy plans public and prevention and management of waste from construction and demolition. I performed simultaneously with the case study presenting other specialty projects for different types of construction work